IgE-Mediated Anaphylaxis to Foods, Venom, and Drugs: Influence of Serum Angiotensin Converting Enzyme Levels and Genotype. (19th December 2012) - Varney, V. A.; Warner, A.; Ghosh, A.; Nicholas, A.; Sumar, N.
Abstract : Circulating angiotensin-II protects the circulation against sudden falls in blood pressure and is generated by the enzymatic action of angiotensin converting enzyme (ACE) on angiotensin-I. The ACE genes have 2 allelic forms, "I" and "D." The "D" genotype has both highest angiotensin-II generation and serum ACE levels compared to "I". 120 patients with IgE-anaphylaxis, 119 healthy controls, and 49 atopics had serum ACE levels, ACE genotype, and renin levels determined. Plasma renin levels were identical for all groups. Serum ACE levels and genotypes were similar for healthy controls (HC) and atopics, but lower in anaphylaxis (P = 0.012 ), with ACE genotypes also showing increased "I" genes (P = 0.009 ). This effect was more pronounced in subjects manifesting airway angioedema and cardiovascular collapse (AACVS) than mild cutaneous and respiratory (CRA) symptoms. AACVS was significantly associated with the presence of "I" genes. For "ID" genotype OR is 5.6, 95% CI 1.8 to 17.4, and for "II" genotype OR is 44, 95% CI 5 to 1891 within the anaphylaxis group = 0.001. The results show a difference in the genotype frequency between control and anaphylaxis, suggesting a role for the renin angiotensin system in anaphylaxis manifesting with airway angioedema and cardiovascular collapse.